Organization and consolidation in community enterprises in Sierra Gorda, Querétaro, Mexico - Mata-Arratia, Eduardo (2024)
Introduction: Since the COVID-19 crisis, tourism has been one of the main activities that adapt to the needs of the market. Community enterprises showed a high degree of resilience to this event, as tourists began to seek contact with nature and places far from urbanization. Objective: To build analysis categories to determine the level of organization and consolidation of five community enterprises in the Sierra Gorda of Querétaro, Mexico. Methodology: Participatory Action Research (PAR), which consists of the construction of knowledge from intervention in the territory, starting from a participatory diagnosis, theoretically analyzing and proposing alternative solutions based on theoretical knowledge and the perspective of the communities. Conclusions: Four levels of consolidation were obtained, and eight categories based on the axes of sustainability. It is concluded that it is necessary to support community enterprises to strengthen their organizational structure and achieve collaboration and cooperative networks that allow their development and subsistence in the face of crises.